PERAN UNIT PATROLI SABHARA DALAM MENCEGAH TINDAK PIDANA CURANMOR RODA DUA DI WILAYAH HUKUM POLRES CIMAHI - Arie Satria Putra dedi family (Advances in Police Science Research Journal, 2020)
The frequent occurrence of crime of theft is motivated by the necessities of life from the community, especially theft of motor vehicles, especially for two wheels in the area of ​​West Java, namely Cimahi. The police institution, especially the Sabhara unit, is required to carry out its duties to conduct surveillance in the form of patrol. The purpose of this study was to analyze how the role of the Shabara unit was in preventing criminal acts, describing the factors that caused the occurrence of criminal acts and describing the constraints to the implementation of patrols in order to prevent criminal acts of two-wheeled curanmor in the Cimahi Regional Police.This type of research is a qualitative research with field research methods. The location of this research is in the Cimahi Regional Police Office. Data collection techniques are done by observation, interviews and document studies. Data were analyzed using the techniques of collecting, reducing, displaying data and drawing conclusions.The results of this study indicate the role of patrol conducted by the Cimahi Police Sabhara Unit is to make local vulnerability data, the implementation of the patrol carried out in accordance with the hotspot data. Factors that influence the occurrence of theft due to the lack of maximum prevention carried out by the Sabhara Unit and the situation that supports the perpetrators of the action and the owner of the vehicle of the number of motorized vehicles that increase every year. Factors which become obstacles in carrying out its role are the lack of personnel of the Sabhara Unit, lack of fuel budget and the ability of the patrol personnel themselves. External factors originating from the Cimahi City community are still lacking in legal awareness. Keywords: Curanmor, Patrol, Unit Sabhara, Cimahi Regional Police